"Hitlermania": Nazism and the Holocaust in Indian History Textbooks. Issue 1 (1st March 2020) - Banerjee, Basabi Khan; Stöber, Georg
Abstract: Recent surveys and reports document a growing phenomenon of "Hitlermania" in some parts of India. This article investigates whether the way in which National Socialism is presented in school education has encouraged this development or, on the contrary, has discouraged a positive valuation of the Nazis, including their leader. It analyzes curricula and a sample of school history textbooks published by state and central education boards, which have been used in Indian schools over the last two decades, focusing on their treatment of National Socialism and the Holocaust. While the results can be partly attributed to government interference in the school history curricula and in textbook writing, there appear to have been other factors at play, such as the social environment.